Investigating the relationships between economic growth and environmental degradation: Evidence from EU15 countries - Hatmanu, Mariana; Cautisanu, Cristina (Technological and Economic Development of Economy, 2023)
The Environmental Kuznets Curve (EKC) hypothesis has become a centre of interest for empirical research, as it serves to identify the relationships between economic growth and environmental degradation that will lead to a sustainable development path. The aim of the paper is to investigate these relationships for each of the EU15 countries, which are responsible for the largest amount of carbon dioxide emissions in Europe. Based on the results of the analysis of ARDL bounds cointegration approach, for the 1960–2019 period, it was found that there is a great diversity between the countries in the EU15 regarding the existence and shape of EKC, from the identification of N shape, Inverted U-shape or monotonic relationships to the absence of statistically significant relationships. Thus, there are countries that have managed to implement environmental protection measures early and now ensure GDP growth while significantly reducing CO2 emissions. The similarities and differences identified among EU15 countries can serve as a guide for EU policymakers in developing recommendations adapted to specific situations in order to facilitate economic growth taking into consideration environmental protection.first published online 01 December 2022